The Interface Between Constitutional Duty, Constitutional Liability and Criminal Liability: A Comparative Analysis of Standards for High-Ranking Public Officeholders (Poland–Hungary) - Weronika Pietras („Law • Education • Security”, 2026)
The article presents a comparative analysis of the norms concerning constitutional obligations and the regimes of constitutional and criminal liability of the highest public officials in Poland and Hungary. It outlines the scope of these persons' constitutional duties and the mechanisms for holding them accountable for violations of the law, both in terms of constitutional and criminal liability. In this regard, the institution of formal and material immunity, as an instrument balancing the need to secure the exercise of public functions with the rule of law, is analysed. The study further examines the relationship between the constitutional duties of persons holding the highest offices in the state and constitutional and criminal liability.